2021
DOI: 10.3389/fbuil.2021.631307
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and Recyclability of a Functional Jute-Based Geopolymer Composite

Abstract: This study describes the properties of geopolymer composites reinforced with bidirectional jute fibers. Their flexural strength is 12 MPa, four times higher than the strength of non-reinforced reference geopolymers. The bidirectional jute-reinforced geopolymer composite (JGC) is characterized by ductility and high elongation as well as strain hardening with a modulus of 66 MPa. It is found that the introduction of bidirectional jute fibers in the geopolymer matrix increases the adsorption capacity of Cr ions f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Alshaaer worked with the synthesis and recyclability of jute-reinforced geopolymers composites and reported four times higher flexural strength of jute-reinforced geopolymers composites as compared to non-reinforced geopolymers composites. Their results are illustrated in Figure 14 [ 147 ].…”
Section: Geopolymers and Natural Fiber-reinforced Compositesmentioning
confidence: 99%
“…Alshaaer worked with the synthesis and recyclability of jute-reinforced geopolymers composites and reported four times higher flexural strength of jute-reinforced geopolymers composites as compared to non-reinforced geopolymers composites. Their results are illustrated in Figure 14 [ 147 ].…”
Section: Geopolymers and Natural Fiber-reinforced Compositesmentioning
confidence: 99%
“…In this case, it is possible to reflect on the merits of pretreating the fiber by soaking it in water or low-molar alkali, as appropriate, before applying it to the composite, which may improve the continuity of the material. The other research with applying natural fibers in geopolymers confirm that cohesion between fiber and matrix could be improved by using proper pre-treatment [ 25 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…While for NFRGC prepared with sisal fibres, the highest flexural strength was obtained with the addition of 3% fibre content. Similarly, Alshaaer (2021) reported that the flexural strength of NFRGC containing jute fibres was four times higher than the strength of the geopolymer matrix without fibres. The ultimate flexural stress of the plain geopolymer was 3 MPa.…”
Section: Compressive Strengthmentioning
confidence: 93%